Editor's Foreword - Vadim Radaev (Journal of Economic Sociology, 2022)
It is with great sadness that we share the news that Professor Nigel Dodd passed away in August 2022. Nigel Dodd was a Professor of Sociology at the LSE. He obtained his Ph.D. from the University of Cambridge in 1991 with Anthony Giddens as Supervisor, and lectured at the University of Liverpool before joining the LSE in 1995. Nigel’s main interests were in the sociology of money, economic sociology, and classical andcontemporary social thought. He was the author of The Sociology of Money and Social Theory and Modernity (both published by Polity Press). His most recent book, The Social Life of Money, was published by Princeton University Press in 2014. Nigel Dodd was also co-editor (with Patrik Aspers) of Re-Imagining Economic  Sociology, published by Oxford University Press in 2015. Professor Dodd was editor-in-chief of the British Journal of Sociology from 2014 until 2022. He made major contributions to the sociology of money. He was a wonderful and pleasant person we have known for many years.